Upconversion Luminescence Imaging of Tumors with EGFR-Affibody Conjugated Nanophosphors. (2019) - Badieirostami, Majid; Carpenter, Colin; Pratx, Guillem; Xing, Lei; Sun, Conroy
ABSTRACT: Near infrared (NIR) optical imaging has demonstrated significant potential as an effective modality for cancer molecular imaging. Among various NIR probes currently under investigation, upconversion nanophosphors (UCNPs) possess great promise due to their anti-Stokes emission and sequential photon absorption which result in superior detection sensitivity and a simple imaging setup, respectively. Here we investigated the utility of this imaging modality to detect tumor cells expressing the epidermal growth factor receptor (EGFR) using affibody functionalized nanophosphors and a custom built imaging system. Initially, aqueous dispersible NaYF4 : Tm +3, Yb +3 UCNPs were synthesized and their photophysical properties were characterized. Then, their luminescence response as a function of concentration and their depth resolving capability in a tissue-simulating phantom were examined. Finally, we demonstrated the use of bioconjugated UCNPs for imaging EGFR-expressing tumors both in vitro and in vivo. Our data suggests that NIR imaging with UCNPs may be useful for noninvasive imaging of tumors.